Balance de las capacidades de poder entre Chile y Argentina: análisis comparativo 1978-2003 - Faundes, Cristián (UNISCI Discussion Papers, 2007)
This research arises from the constant need for measuring the power capabilities between neighbouring countries. A comparative analysis from the perspective of international relations has been chosen, focused on three processes that started simultaneously in the selected 25 years period: change in the international system, Chile’s accelerated rise, and fast rapprochement between both nations from 1984. This allows for the development of a complex interdependence that on the long term leaves the control of the natural gas that supplies 19 per cent of Chile’s energy consumption in the hands of Buenos Aires. The data indicate that in that quarter of a century Chile increased its relative power to the point of surpassing its neighbour’s power capabilities; however, it is subject to Argentina’s limitations to the supply of energy resources.